Rule-Based Integration of Domain-Specific Modelling Languages - Braatz, Benjamin; Brandt, Christoph (Electronic Communications of the EASST, 2011)
Domain-specific modelling languages (DSMLs) can increase the acceptance of (semi-)formal modelling techniques. They allow all stakeholders in an application domain to participate in the modelling process using notations that are close to their understanding of the domain. When several groups of stakeholders are concerned with a certain aspect of the modelled system, the question arises how different DSMLs can be integrated with respect to this aspect. In this paper, we propose rule-based transformations as a means to integrate heterogeneous DSMLs overlapping on dedicated aspects. We illustrate the approach by a running example of a small visual DSML for IT landscapes and a textual DSML for firewall configurations.